The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Remote sensing of ice albedo using harmonized Landsat and Sentinel 2 datasets: validation - Shunan Feng; Joseph Mitchell Cook; Yukihiko Onuma; Kathrin Naegeli; Wenxia Tan; Alexandre Magno Anesio; Liane G. Benning; Martyn Tranter (International Journal of Remote Sensing, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Sex-related differences in the antinociceptive effects of opioids: importance of rat genotype, nociceptive stimulus intensity, and efficacy at the µ opioid receptor - Charles D. Cook; Andrew C. Barrett; Emily L. Roach; Joseph R. Bowman; Mitchell J. Picker (Psychopharmacology, 2000)